Data on the creation of new protected areas in the Nadym district of the Yamal-Nenets Autonomous Okrug - Glazunov Valerii (EDP Sciences, 2021)
The protected areas of the Nadym district are currently represented by only one nature reserve «Nadymskiy». This does not protect the biodiversity of the region. In 2020, we conducted a survey of the Nadym district in order to find new sites for the creation of protected areas. As a result, 7 new protected areas have been proposed: a natural park, a wildlife sanctuary and 5 natural monuments, including three lakes with a rare protected species of spore plants – Isoetes echinospora. The proposed protected areas cover the biodiversity of all natural zones of the Nadym district: tundra, forest-tundra and northern taiga. Some of the protected areas are of great historical and cultural importance for the aborigines.